Predicting resectability after neoadjuvant chemotherapy for patients with borderline resectable pancreatic cancer: a single center, retrospective trial - Schepp, Florian; Hempel, Sebastian; von Bechtolsheim, Felix; Merboth, Felix; Radulova-Mauersberger, Olga; Teske, Christian; Mibelli, Nicolas; Seifert, Lena; Weitz, Jürgen; Distler, Marius; Oehme, Florian (Frontiers in Oncology, 2025)
Background/ObjectivesPancreatic ductal adeno carcinoma (PDAC) in its borderline resectable (BR) stage often limits the possibility of complete resection, currently the only potential path to a cure. Neoadjuvant chemotherapy seeks to downsize tumors, thereby increasing the chances of achieving an R0 resection. However, accurately predicting resectability following such treatment remains challenging. This study aims to identify and evaluate potential biomarkers that may improve preoperative assessment of tumor resectability during exploratory laparotomy, thereby minimizing the incidence of futile surgical interventions and their associated morbidity in patients with non-resectable malignancies.MethodsWe conducted a retrospective analysis of all patients who underwent exploratory laparotomy following neoadjuvant chemotherapy at the Department of Visceral, Thoracic, and Vascular Surgery, University Hospital Dresden, between 2011 and 2022. Employing a propensity score matching, we compared patients with resectable and unresectable pancreatic cancer. The primary endpoint was to evaluate preoperative parameters for predicting resectability status.ResultsThis study included initially 134 patients with neoadjuvant treated BR PDAC who underwent exploratory laparotomy. Among them, 100 (74.6%) underwent curative intended resection, and 34 (25.4%) had an explorative laparotomy only. After Propensity Score Matching we found that a pre-chemotherapy CA 19–9 Value < 450 U/ml (OR 2.9; 95% CI: 1.04 – 8.53, p = 0.04), a pre-operative CA19–9 value of < 105 U/ml (OR 13.9; 95% CI: 3.88 – 49.7, p = 0.001), and a pre - to post-chemotherapy CA19–9 ratio of ≤ 15% (OR 9; 95% CI: 2.48 – 32.7, p = 0.001) raised the odds for resectability. Further, if the combination of a preoperative CA 19-9 < 105 U/ml and a pre - to post-chemotherapy CA19–9 ratio of < 15% was present, the resectability rate increased up to 93%, compared to 30% when both parameters were above the threshold. This specific constellation was a significant predictor (OR 63; 95% CI: 7.84 – 506, p = 0.001) for curative resectability.ConclusionsOur data highlight not only the significant role of the preoperative CA19–9 value and the pre- to post-chemotherapy CA19–9 ratio but, even more importantly, emphasize the critical impact of the combination of these two parameters on the resectability of BR-PDAC.